PENINGKATAN PENGETAHUAN DAN KETERAMPILAN PETERNAK DESA TAKMUNG KLUNGKUNG MELALUI SOSIALISASI PEMELIHARAAN KAMBING PE BERORIENTASI AGRIBISNIS - N M., Artiningsih; Sukarini, I A.M.; Putra, S.; Martini, H.; Subhagiana, W. (Buletin Udayana Mengabdi; Vol 10 No 2 (2011): Jurnal Udayana Mengabdi, 2012)
Natural resources of Klungkung regency particularly at Takmung village according to Bali forages survey in 1992, was very potencial for developing farm animals (goat and cow) due to its highest forages production especially green legumes. Those potencial however, were not optimally used by the farmers which lead to the unsuccessful production attainment. Due to this condition, the community service for farmers at Takmung village, howevr was conducted on 13th August 2010. The aim of this activity was to deepen their knowledge and skill particularly with more emphases on the agribisnis aspect of farm management. The method used is by socialization in rearing and management practices of PE goat as one of the promising commodity in order to increase milk and meat production both in quantity and quality. In this activity include discussion and demonstration how to compose concentrate and forage ration adequately, how to attain fresh, clean and healthy milk from the dam goat. Twenty eight farmers were involved as participants with 5 presenters as lectures or instructors. According to the evaluation results during this activity, the participants were very enthusiastic which can be seen by a lot of questions raised during discussion session, as well as during demonstration practices. Results from pre and post-test evaluation suggests that the participants improved their knowledge and skill for those 5 aspects: in slection, feed and nutrition, reproduction, milk production and handling, and waste product handling and fertilizer were increased 27,76%, 33,33%, 27,77%, 5,55%, and 16,67% respectively. From these results it can be suggested that in this services our innovation can be adopted by the farmers and hopefully they can implement practically in the field. We also suggest that they could form a strong and professional farmer group which are also provided to spread out this innovation among their communities.